2016
DOI: 10.17221/167/2015-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

A rare radiographic appearance of a calcified uterus in a queen with pyometra: a case report

Abstract: This report describes the clinical presentation, diagnosis and treatment of a queen with open pyometra. Lethargy, anorexia and previous treatment failure were the main reasons resulting in referral for diagnostic evaluation. The history, haematological and biochemical profiles and abdominal radiographs revealed open pyometra. Following ovariohysterectomy and antibiotic therapy there was total resolution of clinical signs. Histopathology of the uterus showed severe calcification. The unique part of this report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Dystrophic mineralisation has also been described in a canine uterine leiomyosarcoma 11 ; furthermore, generalised endometrial mineralisations related to long‐term progesterone administration have been reported in a bitch with pyometra 12 and in other bitch with cystic endometrial hyperplasia–pyometra complex and an ovarian granulosa cell tumour 13 . However, in these cases, mineralisations appeared on ultrasonography as echogenic pinpoint or straight endometrial foci or stippled hyperechoic lesions, accompanied by mild acoustic shadowing and comet tail artefact rather than C‐shaped structures.…”
Section: Discussionmentioning
confidence: 98%
“…Dystrophic mineralisation has also been described in a canine uterine leiomyosarcoma 11 ; furthermore, generalised endometrial mineralisations related to long‐term progesterone administration have been reported in a bitch with pyometra 12 and in other bitch with cystic endometrial hyperplasia–pyometra complex and an ovarian granulosa cell tumour 13 . However, in these cases, mineralisations appeared on ultrasonography as echogenic pinpoint or straight endometrial foci or stippled hyperechoic lesions, accompanied by mild acoustic shadowing and comet tail artefact rather than C‐shaped structures.…”
Section: Discussionmentioning
confidence: 98%